THE RELATIONSHIP BETWEEN ECTOPARASITES AND THE GROWTH OF SEAWEED (KAPPAPHYCUS ALVAREZII) CULTIVATED IN THE WATERS OF MANDALLE VILLAGE, PANGKAJENE ISLANDS REGENCY - Irfani Baga; Mohamad Adnan Baiduri; Rusli Rusli (ITScience (Information Technology and Science), 2023)
This study aims to determine the types of ectoparasites found in the thallus of cultivated seaweed Kappaphycus alvarezii and their effect on their growth. The research will be conducted in the seaweed cultivation area of Mandalle Village, Pangkajene Islands Regency. The determination of research stations was carried out purposively (purposive sampling) for three representative aquaculture stations. This is so that it can represent or describe the condition of the waters of Mandalle Village. The cultivation method used in this study was the long line method as used by residents around the study site. Maintenance construction as a sampling unit at each station point, in the form of a 25-meter long rope span of 10 ropes with a distance between the ropes of 1 m. Each stretch rope contains 100-120 seedling clumps with a distance of 20 cm between the straps. Seaweed seeds with an initial weight of 50-70 grams, tied to clump ropes. Planting of seeds is carried out at a depth of 30 cm from the surface of the water. The cultivation construction distance is installed as far as 700-1000 m from the beach. Observation of growth is done by measuring the weight of each clump or the overall weight of each clump of each span rope, at the end of each maintenance cycle. The data obtained for 45 days is then calculated using the growth formula. Seaweed samples for observation of ectoparasites were taken at 3 (three) points of the cultivation area for each bundle of seaweed. The entire surface of the sample thallus was observed with the naked eye and the loop. The results of this study indicated that all observation stations on the South, North and West coasts were dominated by barnacle ectoparasites, followed by green mussels and worms with a total percentage of 90%. While the absolute growth between all stations is relatively the same.